2018
DOI: 10.1126/sciadv.aau4869
|View full text |Cite
|
Sign up to set email alerts
|

New bounds on dark matter coupling from a global network of optical atomic clocks

Abstract: The first Earth-scale quantum sensor network based on optical atomic clocks is looking for dark matter candidates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 39 publications
(102 reference statements)
4
129
0
Order By: Relevance
“…In the case of domain walls, existing ground-based laser interferometers are particularly sensitive to domain walls with transverse sizes of up to several km, offering a sensitivity of up to 8 orders of magnitude beyond all other existing experiments and measurements [10,[55][56][57][58]. The Fermilab holometer, with its two co-located Michelson interferometers, and especially a global network of laser interferometers would benefit from their ability to disentangle correlated domain-wall-induced signatures from uncorrelated noise sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of domain walls, existing ground-based laser interferometers are particularly sensitive to domain walls with transverse sizes of up to several km, offering a sensitivity of up to 8 orders of magnitude beyond all other existing experiments and measurements [10,[55][56][57][58]. The Fermilab holometer, with its two co-located Michelson interferometers, and especially a global network of laser interferometers would benefit from their ability to disentangle correlated domain-wall-induced signatures from uncorrelated noise sources.…”
Section: Discussionmentioning
confidence: 99%
“…The region in grey denotes existing model-independent constraints from astrophysical observations [55] and short-range tests of gravity [55,56]. The regions in yellow denote existing constraints from domain-wall searches using a pair of co-located clocks referenced to a common cavity [10] and via networks of clocks [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore our technique opens the possibility to reach an unexplored region of the parameter space. Finally we also showed that the time delay is measurable for d up to the solar system scale ≡ 10 12 m. However, the strong constraints of [18] and [3,19] along with the models of cosmic evolution rule out the existence of domain walls of large thickness.…”
Section: Quantitative Estimationmentioning
confidence: 62%
“…9 along with existing constraints. This discovery reach includes the possibility of multiple DM interaction events occurring within the time window of the search, which results in a sensitivity that is comparable to that of optical clocks [23,38]. Notice that the projected sensitivity reach in Fig.…”
Section: B Projected Sensitivity and Discovery Reachmentioning
confidence: 91%
“…The shaded blue regions are the constraints coming from astrophysics [44] while the salmon shaded regions are the constraints placed by previous work from the GPS.DM collaboration [14]. The green shaded region contains the constraints placed by optical clock experiments [23], while the yellow region contains the constraints from a global terrestrial network of laboratory clocks [15].…”
Section: B Projected Sensitivity and Discovery Reachmentioning
confidence: 99%